TEACHERS AND PARENTS` PERCEPTIONS OF CONFLICT IN EARLY CHILDHOOD - Amado, Nuno (2014)
The use of violence and bullying towards teachers and peers has been increasing as a manifestation of the existing conflicts in schools. Reardon (1999) stresses that violent behaviour occurs for lack of skills or of knowledge of nonviolent conflict processing and resolution. Considering that anti-social behaviour can be detected at early ages (Keenan e Shaw, 1998) and that children must be helped to find nonviolent alternatives for solving their conflicts, schools have an important role in reducing the risk of pupils becoming violent (Cowie, Dawn & Sharp, 2003). In fact, teachers should be aware of the importance of social and interpersonal skills as a determinant factor for a good accommodation regarding children’s present and future development (Vale & Gaspar, 2004), making early childhood the best ages to introduce conflict resolution skills. As with teachers, parents have a fundament role in the development of conflict management strategies by preschool children (Perlmanm, Garkinfel & Turrell, 2007). Part of a multinational project, this study aims to understand what preschool teachers and parents think about conflict and conflict resolution strategies, and to contrast teachers and parents views on the subject. The results of this project are expected to be the basis for the development of a peace education conflict resolution programme that will have an important application in schools and in teacher training universities.